Nos arredores da Casa do sol: as imagens espaciais no imaginário hilstiano - Ramos, Danielle Stephane (2012)
Hilda Hilst s (1930-2004) poetry is full of images, symbols and archetypes. We intent to investigate these images related to the space. There are a fruitful relationship between space and the construction of Hilst s poetry. She built her house named Casa do Sol in order to completely dedicate to writing and to know herself. This occurred after Hilst contact with the work of the Greek writer Nikos Kazantzakis (1885-1957), who had influenced Hilst s poetry. Kazantzakis defended the importance of being isolated from the world to meet the other and himself. We have no intention of a biographical study of the house, so we intend to analyze it as a symbolic space: the mythical house of the sun. The house figure out in Hilst s poems as a refuge, a space of intimacy and protection. In this space the lyrical persona Ariana and his beloved Dionysus lived a secret life and a secret love. The house is the image of a microcosm (imago mundi) similar to other microcosms knowed by the speaker that walks on his way into outer space. These spaces are the island and the garden and they belong to the same symbolic constellation of the house. By walking the speaker continues the tradition that began with the philosopher Jean-Jacques Rousseau s autobiography The reveries of the solitary walker. This walk becomes a space for reflection and poetic reverie. The space also demonstrate a desire to return to the original space (ab origine) which establishes a conection with the transcendent. Hilst uses the mathematical space and the speaker becomes an architect of a God s idea, founded upon geometric shapes. Unable to name God, the poet wants to materialize the idea of God as a way to approaching with Him. This study will be developed over four chapters which comprise the theoretical approach, the relationship of space images in the creative imaginary of Hilst and the poems analysis that make up the corpus. We selected the series of poems entitled Trajetória poética do ser , Exercícios para uma ideia , besides the poems Ode descontínua e remota para flauta e oboé. De Ariana para Dionísio . These poems are founded on the work Exercícios and Júbilo, memória, noviciado da paixão. To support this study aims we used Gaston Bachelard s work (especially Poetic of space), Gilbert Durand, Mircea Eliade, among others theorists of imaginary and poetry.